The Scarlatti inheritance - Ludlum, Robert, 1927-2001 (Toronto ; New York : Bantam, 1982)
Matthew Caufield, U.S. agent, who has married into the Scarlatti family, is called upon to determine what is happening to the family fortune
Original ed.: New York : World Pub., 1971